1997
DOI: 10.2307/30141980
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination of Healthcare Workers

Abstract: Objective:To assess factors associated with influenza vaccination of healthcare workers.Design:Cross-sectional survey.Setting:University-affiliated Veterans' Affairs medical center.Participants:Staff physicians and nurses employed by the medical center.Methods:A mailed, self-administered questionnaire.Results:The response rate was 38.0%. The mean age of the respondents was 43.6 years, 71.5% were females, and 26.2% were physicians. Nearly all of the practitioners had daily or weekly contact with elderly or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 34 publications
6
77
1
6
Order By: Relevance
“…Once a healthcare worker has been vaccinated against seasonal influenza, this is a strong predictor of seasonal vaccine uptake in subsequent years [8][9][10][11][18][19][20][21]. This study shows that the receipt of previous seasonal vaccine is also strongly associated with a willingness to accept pre-pandemic vaccine.…”
Section: Discussionmentioning
confidence: 90%
“…Once a healthcare worker has been vaccinated against seasonal influenza, this is a strong predictor of seasonal vaccine uptake in subsequent years [8][9][10][11][18][19][20][21]. This study shows that the receipt of previous seasonal vaccine is also strongly associated with a willingness to accept pre-pandemic vaccine.…”
Section: Discussionmentioning
confidence: 90%
“…30 Several Australian and international studies have shown that following one seasonal influenza vaccination, many HCWs will continue to be vaccinated in subsequent seasons, suggesting it is well worth an organisations time to tailor strategies that best suit their individual workforce, particularly focusing on developing a strong culture for new employees. [24][25][26][27]29,32 Many HCWs commented on the lack of privacy, location of administration and the need for greater rotational trolley to their work environment, these are organisational barriers that could readily be addressed in any future influenza vaccination campaigns to improve vaccination rates. This is the first study to explore in depth the attitudes, barriers and motivators toward seasonal influenza vaccine uptake of Australian HCWs working in pediatric and obstetric environments.…”
Section: Facilitatorsmentioning
confidence: 99%
“…While the reasons for and against influenza vaccinations have been well studied in other developed countries, [21][22][23][24][25][26][27][28] it is unclear as to whether these reasons are similar or different in Australian HCWs. Additionally, it is possible that the reasons for and against influenza vaccinations might differ for Australian HCWs serving pediatric 12 or obstetric populations compared with other patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that offering free vaccines to healthcare personnel leads to higher coverage rates [Ohrt and McKinney 1992;Thomas et al 1993;Nafziger and Herwaldt 1994;Nichol and Hauge 1997;Hall et al 1998;Martinello et al 2003]. …”
Section: <001mentioning
confidence: 99%